Evaluation of high pressure water spray systems as a control measure to reduce silica exposure in underground gold mines - Senekal, Hendrik Johannes (My University, 2017)
Gold mining has always played a major role in the South African economy. Unfortunately, workers’ health could be at risk as exposure to respirable quartz could cause silicosis. Silicosis has no cure or treatment and the only means to prevent silicosis is to reduce exposure to as low a level as possible. This study tested the effectiveness of a high-pressure water spray system as an engineering control measure, to reduce respirable dust and respirable quartz concentrations. This intervention produced a mean personal respirable quartz concentration reduction of 87% (p-value of 0.00003). In addition, a reduction of 53% (p-value of 0.04) was observed in the mean static dust concentration measurements taken upstream and downstream of the control measure. Significant improvement in respirable dust and respirable quartz concentrations was observed after the introduction of the high-pressure water spray system. The results from this study indicate that the health risk to underground mine workers could be reduced by implementing a high-pressure water spray system as an engineering control.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Public Health. Johannesburg, September 2017.
Keywords: Silicosis